Effectiveness of antimicrobial formulations for acne based on orange (Citrus sinensis) and sweet basil (Ocimum basilicum L) essential oils - Matiz, Germán; Osorio, María R.; Camacho, Francisco; Atencia, Maira; Herazo, Jennifer (Biomedica, 2012)
Introduction. Currently, the antimicrobial resistance has developed in bacterial strains involved in the development of acne. Therefore, alternatives to antibiotic treatment have become necessary. Objectives. Gel formulations were designed based on essential oils and acetic acid, and their effectiveness was evaluated in patients affected by acne. Materials and methods. Masked simple experimental study of three gel formulations on 28 volunteer patients, separated in four groups of seven patients. Treatments were applied daily for eight weeks and consisted of (1) antibacterial (essential oils), (2) keratolytic medication (3) essential oils mixed with acetic acetic, and (4) kerolytic medication with acetic acid. Weekly checks were conducted to evaluate patient improvement. Results. All groups reported an improvement of the acne condition, which ranged between 43% and 75% clearance of lesions. Evidence of treatment disappeared within minutes, showing little discomfort or side effects after application. Conclusions. The essential oil formulations were chemically and physically stable during application of treatments. This was demonstrated by gas chromatography, where no evidence no change neither the composition profiles of essential oils nor in acetic acid. The results were ranked good to excellent, particularly for the acetic acid mixture, which achieved improvements of 75%. This appeared to be a result of their joint antiseptic and keratolytic activity. Side effects (burning and redness) disappeared within a few minutes of completing the application, therefore, did not interfere with adherence to treatment.